Dialog Kultural: Qaulan Layyina dalam Dinamika Masyarakat Kontemporer - Rejeki, Rahman; Azhar (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
This research aims to determine qaulan layyina as cultural dialogue in the dynamics of contemporary society. This research uses a library method with a descriptive qualitative approach. This research uses primary and secondary data sources, with data analysis techniques that include analysis, description, and comparison. The data obtained was arranged systematically and analyzed using descriptive methods, with the study results presented logically. This research indicates that the principle of qaulan layyina, which emphasizes gentle and affectionate communication, has a central role in forming a positive communication environment. With a focus on gentleness and warmth in speech, this principle promotes interpersonal harmony and is critical to maintaining social balance and preventing conflict. This approach has universal relevance in the context of contemporary society, which is complex and full of differences. Qaulan layyina not only lays the foundation for solid individual relationships but also contributes to forming an inclusive and resilient communication culture. By prioritizing gentleness in communication, this principle encourages dialogue that respects differences, strengthens social solidarity, and creates space for cooperation and shared understanding.